1986
DOI: 10.1139/f86-101
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Analysis of Power Plant Impact on Fish Populations

Abstract: Alewife (Alosa pseudoharengus) and yellow perch (Perca flavescens) abundances, estimated from monthly gillnet and trawl catches at two transects, were monitored before (1973–74) and during (1975–82) operation of the D. C. Cook Nuclear Power Plant, southeastern Lake Michigan. Intervention analysis, a technique which accounts for autocorrelated observations, and analysis of variance (ANOVA) were applied to the monitoring data to assess any plant impact beginning in 1975. Both analyses disclosed no significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
18
1
Order By: Relevance
“…Luksiene & Sandström (1994) found that Rutilus rutilus fail to recruit in areas that are exposed to thermal discharge from a nuclear power station in Sweden. Madenjian et al (1986) found a decreased abundance of Alosa pseudoharengus and Perca flavescens at a nuclear power plant on Lake Michigan when compared to a reference condition. Negative effects of thermal influence on the growth and the spawning period of Micropterus dolomieu were found for the Doré Bay in Lake Huron (Shuter et al 1985).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Luksiene & Sandström (1994) found that Rutilus rutilus fail to recruit in areas that are exposed to thermal discharge from a nuclear power station in Sweden. Madenjian et al (1986) found a decreased abundance of Alosa pseudoharengus and Perca flavescens at a nuclear power plant on Lake Michigan when compared to a reference condition. Negative effects of thermal influence on the growth and the spawning period of Micropterus dolomieu were found for the Doré Bay in Lake Huron (Shuter et al 1985).…”
Section: Discussionmentioning
confidence: 79%
“…Some of these studies refer to the biological features of single species that have been measured or observed in the field, such as early development and distribution (Shuter et al, 1985;Madenjian et al, 1986), reproduction (Luksiene & Sandström, 1994), and life history (Dembski et al, 2006). Others are restricted to laboratory experiments on thermal tolerance (Bennett & Judd, 1992;Mora & Ospína, 2001;Ospina & Mora, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An additional study (Madenjian et al, 1986) looked at the effects of the D.C. Cook nuclear plant on yellow perch. Fish at power plants can be affected not just by thermal discharges, but by being sucked into the cooling water intakes.…”
Section: Discussionmentioning
confidence: 99%
“…The research obtained during the literature search showed that the elevated temperatures in the river produced by the thermal discharge are not elevated enough to cause any stress or possible mortality for any of the species native to the river (Clapp et al, 1997;Holmes et al, 1994;Hosanson, 1977;Madenjian et al, 1986).…”
mentioning
confidence: 99%
“…The removal of fish by power plants with once-through cooling systems has rarely exerted a demonstrable impact on surrounding fish stock sizes (Madenjian et al 1986;Barnthouse et al 2002;Newbold and Iovanna 2007;Greenwood 2008). An exception may be the Diablo Canyon Power Plant in California, U. S. A., which was found to remove about 40% of the clinid kelpfish larvae during entrainment, thereby affecting the adult population (Ehrler et al 2002).…”
Section: Introductionmentioning
confidence: 99%